Effect Of Probiotic Supplementation On Milk Yield And Its Composition In Buffaloes (Bubalus Bubalis) - Tewari, Dharmesh; Jain, R.K.; Patil, Nagendra; Mudgal, Vishal; Haq , Zulfqar ul (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
The study on effect of probiotic supplementation on milk yield showed that the average daily milk yield was higher (P<0.05) in treatment group (10.58±0.25 liter) compared to the control group (8.88±0.29 liter), but the composition of milk remained unaffected between the two groups with lactose (6.00±0.10 vs. 6.16±0.12 %), fat (6.65±0.10 vs. 6.82±0.15 %) and protein (3.92±0.06 vs. 3.88±0.08 %) content of milk between control vs. treatment groups.